Arrival Angle and Travel Time Measurements of HF Transequatorial Propagation for Plasma Bubble Monitoring. Issue 11 (5th November 2018) - Saito, Susumu; Yamamoto, Mamoru; Maruyama, Takashi
Abstract: A system to measure travel times of high‐frequency (HF) radio waves was developed based on a digital receiver technique. Travel times of HF transequatorial propagation (HF‐TEP) of signals of Radio Australia from Shepparton (36.2°S, 145.3°E), Australia to Oarai (36.3°N, 140.6°E), Japan, were measured by the system. Directions of arrival of the signals were simultaneously observed by a HF Direction Finder located at Oarai (Oarai Direction Finder: ODF). When the ODF observed signals arriving from great circle direction, constant multiple discrete values of propagation times were observed. After sunset, propagation times longer than those expected from the great circle propagation were observed and the ODF observed corresponding signals from off‐great‐circle directions (off‐great‐circle propagation). The observed maximum azimuth angle deviation (∼50°) was much larger than the angle that would have been obtained when a single side reflection in HF‐TEP was assumed. This result supports the multireflection model of off‐great‐circle propagation of HF‐TEP proposed by Tsunoda et al. (2016a, https://doi.org/10.1002/2015JA021695). The propagation time measurements are useful to determine the propagation paths, when they are used with HF‐TEP observations by a HF Direction Finder system. Ray tracing analysis with the propagation times and arrival angles will contribute to monitoring locations of plasma bubbles as well as understanding their structures and the physics behind them. The technique can also be applied to determine the propagation paths in the normal great circle propagations and other geophysical phenomena, such as midlatitude trough, deep traveling ionospheric disturbance modulation of the ionospheric height due to Perkins instability and sporadic E layer irregularities. Key Points: An HF propagation time can be measured with low‐cost devices Transequatorial propagation of HF radio waves is simultaneously measured by a direction finder and a propagation time measurement system Measurements in the arrival angles and travel times of HF off‐great‐circle propagation indicate multiple reflections along the propagation paths